It matters where you graduate from and how good you are: recent findings from two Malaysian universities - Soon, Jan Jan (2018)
Using a 2016/2017 unique dataset of 1,107 freshly minted university graduates sampled from a public and a private university in Malaysia, this paper deals with the intricate recent issue of batches of university graduates’ demand for better starting salaries.We examine whether their salaries are associated with academic performance in the form of CGPA, and which type of institution they graduated from, i.e. a public or private university.Estimation results reveal that these are two statistically significant determinants of the graduates’ starting salaries.Our results are robust to different model specification and different sets of controls. The results support the conventional perception that top academic performers and where you graduate from are indeed crucial to having a good salary prospect. As an aside, claims of gender wage discrimination are not substantiated by our empirical findings, i.e. gender shows no statistical significance on salaries.